Does parental monitoring and disapproval explain variations in alcohol use among adolescents from different countries of birth?. (24th May 2016) - Chan, Gary C. K.; Kelly, Adrian B.; Connor, Jason P.; Hall, Wayne D.; Young, Ross McD.; Williams, Joanne W.
Abstract: Introduction and Aims : This study investigated the extent to which parental monitoring and parental disapproval of alcohol use account for the association between country of birth and adolescent alcohol use. Design and Methods : The sample consisted of 10 273 adolescents from grades 7 (Mean age = 12.5 years), 9 (14.5 years) and 11 (16.4 years) in Victoria, Australia. Participants completed a questionnaire during class time. Mediation analyses were performed to examine the extent to which parental monitoring and parental disapproval of alcohol use accounted for variations in past 30 day alcohol use between Australian‐born and immigrant adolescents. Results : Alcohol use in the past 30 days ranged from 8.0% to 44.4% for participants from different countries/regions of birth. Those born in Asia (odds ratio 0.20–0.51, P < 0.05) and Africa (odds ratio 0.45, P < 0.01) were much less likely to have consumed alcohol compared to those born in Australia. Adolescents from these two regions (except for Western Asia) reported higher levels of parental monitoring and parental disapproval of alcohol use (P < 0.05). Higher levels of parental monitoring and parental disapproval of alcohol use partially mediated the association between birth place and alcohol use (P < 0.05). Discussion and Conclusions : There were large variations in alcohol use between Australian‐born and immigrant adolescents from different countries/regions. Adolescents from Asia or Africa were much less likely to consume alcohol, and this protective effect was partially accounted for by parental monitoring and disapproval of alcohol use.[Chan GCK, Kelly AB, Connor JP, Hall WD, Young RM, Williams JW. Does parental monitoring and disapproval explain variations in alcohol use among adolescents from different countries of birth? Drug Alcohol Rev 2016;35:741–749]